Effects of dietary copper sources and levels on growth performance, copper digestibility, fecal and serum mineral characteristics in growing pigs - Byeonghyeon Kim; Jin Young Jeong; Seol Hwa Park; Hyunjung Jung; Minji Kim (Journal of Animal Science and Technology, 2022)
This experiment was conducted to investigate the effects of three different copper (Cu) sources (one inorganic and two organics) and levels (0, 50, and 100 mg/kg) on the growth performance, Cu digestibility, fecal mineral excretion, serum mineral concentration, jejunal morphology, and serum biochemical profile of growing pigs. A total of 42 male, growing pigs (31.08 ± 1.82 kg) were randomly assigned to seven treatments consisting of one negative control (0 mg/kg of added Cu level) and treatments with copper sulfate (CuSO4), Cu-amino acid complex (CuAA), and Cu-hydroxy-4-methylthio butanoate chelate complex (CuHMB) at 50 and 100 mg/kg each for 28 d. Pigs fed 50 or 100 mg/kg of Cu showed improved (p < 0.05) average daily gain and feed intake. Although Cu excretion decreased (p < 0.01) in pigs fed 100 mg/kg of organic Cu sources compared to those fed CuSO4, there was no difference between the Cu sources in pigs fed 50 mg/kg. However, the apparent total tract digestibility of Cu increased (p < 0.01) in pigs fed organic Cu sources compared with that in pigs fed CuSO4. The addition of CuHMB increased (p < 0.01) serum phosphorus and sulfur concentrations; however, there were no effects of source and level on jejunal morphology and serum biochemical profile. These results suggest that the inclusion (50 mg/kg) of organic Cu sources (CuAA and CuHMB) in the growing pig diet could be beneficial for growth performance and Cu availability and may reduce environmental pollution.